Reconceptualizing Kurikulum Berbasis Cinta: English Teachers' Cognition and Classroom Implementation - Faqih Luthfia, Ayaza; Faisal, Faisal (Universitas Jambi, Magister Program of English Education Department, 2026)
Kurikulum Berbasis Cinta (KBC) has recently been introduced by the Indonesian Ministry of Religious Affairs as a value-oriented curriculum promoting empathy, respect, compassion, and meaningful relationships in education. Although previous studies have examined KBC from the perspectives of character education and classroom implementation, limited attention has been given to how English teachers interpret its principles and translate them into English language teaching. This study explored English teachers' cognition of KBC, its classroom implementation, and the challenges encountered during practice. Employing a qualitative descriptive design, the study involved four English teachers from two Madrasah Tsanawiyah (MTs) in Cilacap Regency, Indonesia. Data were collected through semi-structured interviews, classroom observations, and lesson plan analysis and analyzed using thematic analysis. The findings revealed that teachers perceived KBC as an educational approach integrating character development with English language teaching through supportive teacher–student relationships, collaborative learning, and meaningful classroom interaction. Teachers also integrated KBC values through interpersonal, transactional, and functional texts in the Capaian Pembelajaran (CP) Phase D English curriculum while adapting instruction to students' diverse characteristics, learning readiness, and limited instructional time. Viewed through the lens of teacher cognition, the findings demonstrate that teachers actively interpreted KBC principles and translated them into context-sensitive pedagogical practices. This study contributes to teacher cognition theory by showing that implementing a value-based curriculum is a process of teacher sense-making, through which teachers reinterpret curriculum principles and transform them into context-sensitive communicative pedagogical practices.